1999
DOI: 10.1106/w1h4-7xrw-tpuh-7rka
|View full text |Cite
|
Sign up to set email alerts
|

On the Integration of Piezoceramic Actuators in Composite Structures for Aerospace Applications

Abstract: Up to now experimental and theoretical research on active structures for aerospace applications has put the focus mainly on surface bonded actuators. Simultaneously piezoceramics became the major type of actuating device being investigated for smart structures. In this context various techniques of insulating, bonding and operating these actuators have been developed. However, especially with regard to actuators, only a few investigations have dealt with embedding of these components into the load bearing stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 11 publications
0
9
0
2
Order By: Relevance
“…A review on the state-of-the-art of smart systems with emphasis on rotorcraft has been given by Chopra 7 and on composite structure by Durr 8 .…”
Section: Review Papermentioning
confidence: 99%
See 1 more Smart Citation
“…A review on the state-of-the-art of smart systems with emphasis on rotorcraft has been given by Chopra 7 and on composite structure by Durr 8 .…”
Section: Review Papermentioning
confidence: 99%
“…Adhesive bonding is the most convenient method to bond actuators, since these may be cured at room temperature, and hence, have small residual stresses. A detailed study of the effect of bonding layer thickness was reported by Durr 8 . Bonding layer thickness up to 200 as found in common applications results in a moderate loss in efficiency of 11 per cent to 17 per cent.…”
Section: Bonding Layer Effectmentioning
confidence: 99%
“…(Moses, 1999). gain was varied from 0 to 20 [Figure 29(b)]. A comprehensive analysis of the design and fabrication issues associated with transferring these proof-of-concept results to operational aerospace structures was presented by Durr et al (1999).…”
Section: Active Suppression Of Tail Buffetingmentioning
confidence: 99%
“…Um outro grande programa envolve pesquisas para controle ativo de buffeting utilizando materiais piezelétricos nas empenagens verticais da aeronave F/A-18 (MOSES, 1997(MOSES, , 1999DÜRR, 1998;HOPKINS et al, 1998). Estes estudos apresentam testes em túnel de vento com um modelo de aeronave em escala dinâmica (MOSES, 1997), até ensaios em solo com uma aeronave real (MCGOWAN et al, 1998;HOPKINS et al 1998;MOSES, 1999).…”
Section: Controle Ativo Utilizando Materiais Piezelétricosunclassified
“…Por exemplo, o controle ativo de flutter utilizando atuadores piezelétricos apresentado por Heeg (1993), o programa da NASA "Piezoelectric Aeroelastic Response Tailoring Investigation (PARTI)" desenvolvido para controle de flutter e atenuação da resposta a rajada (MCGOWAN et al, 1998) e os trabalhos apresentados para controle ativo de buffeting utilizando materiais piezelétricos nas empenagens verticais da aeronave F/A-18 (MOSES, 1997(MOSES, , 1999DÜRR, 1998;HOPKINS et al, 1998). Uma revisão bastante abrangente sobre o uso de materiais inteligentes em soluções de problemas aeroelásticos é apresentada por Giurgiutiu (2000).…”
Section: Introdução Introduçãounclassified